Microscopic dispersion detection method for carbon black in rubber
By spreading rubber samples with liquid paraffin oil and observing with transmitted light under a microscope, the high cost and low accuracy of carbon black dispersion detection in rubber in the prior art is solved, and a more accurate and economical carbon black dispersion detection method is achieved.
Patent Information
- Application Number
- CN202411991218.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The existing methods for detecting carbon black dispersion in rubber have problems such as high cost, poor popularity, high experimental costs, and the inability to characterize the dispersion of carbon black in rubber.
The rubber sample slices were spread out by liquid paraffin oil, combined with the transmitted light observation under the microscope, the pictures were collected and the area percentage of carbon black aggregates were calculated, thereby calculating the carbon black dispersion.
The calculation accuracy of the percentage of carbon black aggregate area is improved, the calculation formula of carbon black dispersion is simplified, the experimental cost is reduced, and more accurate and specific microdispersion characterization of carbon black in rubber is provided.
Smart Images

Figure CN119804444A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of rubber, and in particular to a method for detecting microscopic dispersion of carbon black in rubber. Background Art
[0002] Carbon black is the most important reinforcing agent for tire products because it can greatly improve the physical properties of rubber. It enhances the strength and wear resistance of rubber and is widely used in various industries.
[0003] The dispersion of carbon black refers to the degree to which carbon black is evenly dispersed in the rubber matrix. The aggregation and accumulation of carbon black particles will affect the dispersion of carbon black. Good dispersion can increase the surface area of carbon black and increase its contact area with rubber, thereby improving the reinforcing effect of carbon black on rubber and reducing the cost of products. On the contrary, poor dispersion of carbon black will lead to the aggregation of carbon black, reduce its surface area, reduce its reinforcing effect on rubber, and reduce the performance and service life of the product.
[0004] Chinese invention patent CN107505480A discloses a method for detecting the dispersion of fillers in rubber composite materials. The method uses an AFM atomic force microscope, which has high cost, poor popularity, expensive spare parts and consumables, and high experimental costs.
[0005] In the rapid comparison method for evaluating the dispersion of carbon black and carbon black / silica in rubber according to GB / T6030-2006, when the various fillers in the rubber are well dispersed, the light reflected from the freshly cut surface of the rubber will show a flat, smooth, and flawless surface. If the fillers in the rubber are not well dispersed, the surface will show annular, convex "lumps" or concave pockmarks. Then the evaluation is carried out according to the standard pictures of different defects. This method is greatly affected by the cross section of the rubber, and this method evaluates the dispersion of all fillers added to the rubber, and cannot characterize the dispersion of carbon black in the rubber alone.
[0006] GB / T18521-2019 Determination of the dispersion of pigments or carbon black in polyolefin pipes, fittings and mixed materials. When this method is used to determine carbon black, this standard is applicable to polyolefin pipes, fittings and mixed materials with a carbon black mass fraction of less than 3%. It is not applicable to the characterization of carbon black dispersion in rubber.
[0007] Method B in ASTM D2663-14: In the method of measuring the number of agglomerates, a freezing microtome is used, followed by transmission observation under a microscope. This method is relatively rough and the researchers have poor repeatability. The use of organic solvents mentioned in the standard, including xylene, toluene, and methanol, helps to spread the slices onto a glass slide, which is beneficial for observation under a microscope. However, experiments have shown that xylene, toluene, and methanol solvents have no effect on the spreading of slices. Among them, toluene and xylene are colorless, transparent liquids that are volatile, have a pungent odor, are highly toxic, and are important hazardous chemicals. Methanol is colorless, transparent, has a pungent odor, and is a toxic gas. Summary of the invention
[0008] To solve the above problems, the present invention provides a method for detecting the microscopic dispersion of carbon black in rubber. Liquid paraffin oil can spread out the rubber sample slices well, and the contours of carbon black and rubber observed under a microscope are clearer, so the calculation of the percentage of the area of the image occupied by carbon black aggregates is more accurate, thereby making the calculation formula of the carbon black dispersion degree simpler.
[0009] The object of the present invention is achieved in the following manner: A method for detecting microscopic dispersion of carbon black in rubber comprises the following steps: (1) Sampling of vulcanized rubber; (2) Freeze the sample to -20 to -70°C below the glass transition temperature and keep it for 13 to 20 minutes, then slice the sample; (3) Take out the cut sample slices, flatten them on a glass slide with liquid paraffin oil, and then observe them under a microscope and collect pictures; (4) Calculate the area percentage of carbon black aggregates with a size of >7 μm in the image based on the image, and thus calculate the area percentage of carbon black aggregates in the rubber; Then calculate the carbon black dispersion, carbon black dispersion (%) = 100 (1-A / B), A is the area percentage of carbon black aggregates in the rubber, B is the volume percentage of carbon black in the compound, B = (rubber density / apparent density of carbon black) × mass percentage of carbon black in the rubber; In step (3), a clean brush is dipped in liquid paraffin oil, and the liquid paraffin oil is brushed evenly on the glass slide. The tip of the brush dipped in liquid paraffin oil is used to take the sample slice from the sample chamber, and then the sample slice is spread and flattened on the glass slide with the tip of the brush.
[0010] In step (3), the dispersion of carbon black in the sample slice is observed under a microscope using transmitted light, and images are collected. For one sample slice, at least 10 images at different positions are collected. In step (4), the area percentage of carbon black aggregates with a size greater than 7 µm in each image is calculated, and the average of the results of the images at different positions is taken, which is the area percentage of carbon black aggregates in the rubber.
[0011] In step (3), the dispersion of carbon black in the sample slices is observed under a microscope using transmitted light, and images are collected. At least two sample slices are observed for one sample, and at least 10 images of different positions are collected for each sample slice. In step (4), the area percentage of carbon black aggregates with a size greater than 7 µm in each image is calculated, and the average of the image results at different positions of each sample slice is taken, which is the area percentage of carbon black aggregates in the rubber.
[0012] In step (2), the sample slice thickness is 2 μm.
[0013] Compared with the prior art, the present invention provides a method for detecting the microscopic dispersion of carbon black in rubber. Liquid paraffin oil can spread out the rubber sample slices well, and the outlines of carbon black and rubber observed under a microscope are clearer, so the calculation of the percentage of the area of the image occupied by carbon black aggregates is more accurate, thereby making the calculation formula of the carbon black dispersion degree simpler. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a picture of the sample slice of Example 1 of the present application under a microscope.
[0015] Figure 2 This is a picture of the sample slice of Example 2 of the present application under a microscope. DETAILED DESCRIPTION
[0016] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that this embodiment is only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Technical personnel skilled in the art can make some non-essential improvements and adjustments based on the above-mentioned contents of the present invention.
[0017] A method for detecting microscopic dispersion of carbon black in rubber comprises the following steps: (1) Sampling of vulcanized rubber; (2) Freeze the sample to -20 to -70°C below the glass transition temperature and keep it for 13 to 20 minutes, then slice the sample; (3) Take out the cut sample slices, flatten them on a glass slide with liquid paraffin oil, and then observe them under a microscope and collect pictures; (4) Calculate the area percentage of carbon black aggregates with a size of >7 μm in the image based on the image, and thus calculate the area percentage of carbon black aggregates in the rubber; Then calculate the carbon black dispersion, carbon black dispersion (%) = 100 (1-A / B), A is the area percentage of carbon black aggregates in the rubber, B is the volume percentage of carbon black in the compound, B = (rubber density / apparent density of carbon black) × mass percentage of carbon black in the rubber; In step (3), a clean brush is dipped in liquid paraffin oil, and the liquid paraffin oil is brushed evenly on the glass slide. The tip of the brush dipped in liquid paraffin oil is used to take the sample slice from the sample chamber, and then the sample slice is spread and flattened on the glass slide with the tip of the brush.
[0018] In step (3), the dispersion of carbon black in the sample slice is observed under a microscope using transmitted light, and images are collected. For one sample slice, at least 10 images at different positions are collected. In step (4), the area percentage of carbon black aggregates with a size greater than 7 µm in each image is calculated, and the average of the results of the images at different positions is taken, which is the area percentage of carbon black aggregates in the rubber.
[0019] Alternatively, in step (3), the dispersion of carbon black in the sample slices is observed under a microscope using transmitted light, and images are collected. For one sample, at least two sample slices are observed, and for each sample slice, at least 10 images of different positions are collected. In step (4), the area percentage of carbon black aggregates with a size greater than 7 µm in each image is calculated, and the average of the image results at different positions of each sample slice is taken, which is the area percentage of carbon black aggregates in the rubber.
[0020] In step (2), the sample slice thickness is 2 μm.
[0021] Compared with the prior art, the present invention provides a method for detecting the microscopic dispersion of carbon black in rubber. Liquid paraffin oil can spread out the rubber sample slices well, and the outlines of carbon black and rubber observed under a microscope are clearer, so the calculation of the percentage of the area of the image occupied by carbon black aggregates is more accurate, thereby making the calculation formula of the carbon black dispersion degree simpler.
[0022] The inventors have found through experiments that the organic solvents xylene, toluene and methanol used in method B of ASTM D2663-14 have no effect on the spreading of slices. Toluene and xylene are colorless and transparent liquids, volatile, with pungent odors and high toxicity, and are important hazardous chemicals. Methanol is colorless and transparent, has a pungent odor and is a toxic gas.
[0023] In addition, we tried to use common organic solvents to spread the sample slices. We found that ethanol is extremely volatile and has low toxicity. It cannot spread the sample slices that have curled up into a ball. Mineral spirits are colorless and transparent liquids. They are not easy to volatilize and have low irritation. However, in the process of spreading the sample, the movement resistance between the rubber ultra-thin sheet and the mineral spirits is large, and it is difficult to spread the sample slices completely. Petroleum ether is a colorless and transparent liquid. It is volatile and toxic. It has no effect on spreading the sample slices. In addition, organic solvents such as n-heptane, cyclohexane, acetone, acetonitrile, isooctane, 2-butanone, dichloromethane, and chloroform cannot spread the sample slices well.
[0024] The inventor has found through numerous attempts that liquid paraffin oil has a good spreading effect on curled samples. At the same time, liquid paraffin oil is not easy to volatilize, and has little harm to the body of the experimenter, and is a relatively green and safe chemical reagent.
[0025] Therefore, the present application provides a method for detecting microscopic dispersion of carbon black in rubber.
[0026] The cryostat used was an RMC cryostat, model CR1000, and the microscope was a Leica microscope, model DM4M. Liquid paraffin oil was purchased from Yantai Shuangshuang Chemical Co., Ltd., with the manufacturer and batch number being 20100503. The boiling point of liquid paraffin oil is 113-144°C or 185-245°C.
[0027] Example 1 A method for detecting microscopic dispersion of carbon black in rubber comprises the following steps: Step 1: Use IRB 8 industrial reference carbon black. The sample preparation is in accordance with GB / T 3780.18-2007 Carbon Black Identification Method in Natural Rubber (NR). The mixing procedure uses the open mill mixing method.
[0028] Step 2: Cut the vulcanized film into samples with a thickness of 2 mm, a width of 3 mm, and a length of 5 mm; Step 3: Freeze the sample to -20°C below the glass transition temperature and keep it for 13 min, then slice the sample; Step 4: Select a sample slice without scratches and with a thickness of 2 μm for spread observation; when sampling, brush liquid paraffin oil evenly on the slide, use the tip of a brush dipped in liquid paraffin oil to take samples from the sample chamber, and then spread and flatten the sample slice on the slide with the tip of the brush; The thickness of the sample slice can be adjusted according to the color depth of the film after vulcanization. If the color is light, the thickness can be increased. For example, if the sample contains a particularly high amount of white carbon black, the thickness of the slice needs to be increased for better transmission observation under a microscope; generally, a thickness of 2 μm can meet the requirements, and 2 μm can meet the requirements for normal rubber products in the tire industry.
[0029] Step 5: Use transmitted light to observe the dispersion of carbon black on the sample slice under a microscope and collect pictures. For one sample slice, take pictures of 10 different positions. The pictures are as follows: Figure 1 As shown; The dispersion of carbon black can be directly observed from the microscope images. When the carbon black is well dispersed, it appears as very small particles, usually less than 7 μm in size.
[0030] When carbon black is not dispersed well, it will aggregate to form carbon black aggregates, and the microscope picture will show a piece or piece of black aggregates.
[0031] Step 6: Carbon black aggregate statistics: Open Image J software and analyze the images at 10 different locations; Calculate the area percentage of carbon black aggregates with a size greater than 7 µm in each image, and take the average of the results of ten images to obtain the area percentage of carbon black aggregates in the rubber.
[0032] Step 15: Calculation of carbon black dispersion: The carbon black dispersion was calculated as the percentage of carbon black area below the agglomerate size of 7 µm.
[0033] Carbon black dispersion (%) = 100 (1-A / B).
[0034] A is the area percentage of carbon black aggregates in rubber, which is the average value of carbon black aggregates calculated in 10 pictures at different positions of a sample.
[0035] B is the volume percentage of carbon black in the compound.
[0036] B = (density of rubber / apparent density of carbon black) × mass percentage of carbon black in rubber.
[0037] As a result, the carbon black dispersion was 98.891%; The carbon black dispersion measured by the existing carbon black dispersion instrument is 7.12; The carbon black dispersion meter is aview manufacturer's equipment, model DG100+: it uses a reflective optical microscope to measure the dispersion of fillers in rubber compounds.
[0038] Example 2 A method for detecting microscopic dispersion of carbon black in rubber comprises the following steps: Step 1: Sample preparation, using N234 carbon black, 12.5%, precipitated silica, 12.5%, rubber, 62.6%, and others, 12.4%. The sample preparation is in accordance with GB / T 3780.18-2007, the identification method of carbon black in natural rubber (NR), and the mixing procedure uses the internal mixer method.
[0039] Step 2: Cut the vulcanized film into samples with a thickness of 2 mm, a width of 3 mm, and a length of 5 mm.
[0040] Step 3: Freeze the sample to -35°C below the glass transition temperature and keep it for 20 min, then slice the sample; Step 4: Select a sample slice without scratches and with a thickness of 2 μm for spread observation; when sampling, brush liquid paraffin oil evenly on the slide, use the tip of a brush dipped in liquid paraffin oil to take samples from the sample chamber, and then spread and flatten the sample slice on the slide with the tip of the brush; The thickness of the sample slice can be adjusted according to the color depth of the film after vulcanization. If the color is light, the thickness can be increased. For example, if the sample contains a particularly high amount of white carbon black, the thickness of the slice needs to be increased for better transmission observation under a microscope; generally, a thickness of 2 μm can meet the requirements, and 2 μm can meet the requirements for normal rubber products in the tire industry.
[0041] Step 5: Use transmitted light to observe the dispersion of carbon black on the sample slice under a microscope and collect pictures. For one sample slice, take pictures of 10 different positions. The pictures are as follows: Figure 2 As shown; The dispersion of carbon black can be directly observed from the microscope images. When the carbon black is well dispersed, it appears as very small particles, usually less than 7 μm in size.
[0042] When carbon black is not dispersed well, it will aggregate to form carbon black aggregates, and the microscope picture will show a piece or piece of black aggregates.
[0043] Step 6: Carbon black aggregate statistics: Open Image J software and analyze the images at 10 different locations; Calculate the area percentage of carbon black aggregates with a size greater than 7 µm in each image, and take the average of the results of ten images to obtain the area percentage of carbon black aggregates in the rubber.
[0044] Step 15: Calculation of carbon black dispersion: The carbon black dispersion was calculated as the percentage of carbon black area below the agglomerate size of 7 µm.
[0045] Carbon black dispersion (%) = 100 (1-A / B).
[0046] A is the area percentage of carbon black aggregates in rubber, which is the average value of carbon black aggregates calculated in 10 pictures at different positions of a sample.
[0047] B is the volume percentage of carbon black in the compound.
[0048] B = (density of rubber / apparent density of carbon black) × mass percentage of carbon black in rubber.
[0049] As a result, the carbon black dispersion was 97.157%.
[0050] The carbon black dispersion measured by the existing carbon black dispersion instrument is 6.31.
[0051] The carbon black dispersion meter is aview manufacturer's equipment, model DG100+: it uses a reflective optical microscope to measure the dispersion of fillers in rubber compounds.
[0052] In order to verify the correlation between the carbon black dispersion instrument and the carbon black micro-dispersion results, we prepared samples with different mixing degrees for the formula sample, and the normal rubber mixing results are as above. The formula sample was plasticized 3 times and 10 times to obtain the carbon black dispersion instrument and carbon black micro-dispersion results, as shown in Table 1 below.
[0053] Table 1 The test method of the existing carbon black dispersion instrument is a well-known method: a section is cut on the vulcanized sample with a sharp blade and the section is placed in front of the test aperture. The light is irradiated on the sample at an angle of 30 degrees. The light irradiated on the smooth area of the sample is scattered, and then the light irradiated on the filler agglomeration is reflected into the camera. A picture is obtained in the camera, and then the picture is processed to remove noise and irregularities on the surface of the sample. The picture is then filtered to obtain a black and white image. The black and white image is used to calculate the dispersion: the white points represent the filler agglomeration, which is dispersed in the black background. The adjacent white points represent the area of the agglomeration, from which the diameter of the agglomeration can be calculated (assuming that the agglomeration is spherical).
[0054] The present invention provides a method for detecting the microscopic dispersion of carbon black in rubber: it uses the transmission of light. Carbon black is a black object, and light cannot penetrate it, so it will appear black. This method can better characterize the microscopic morphology of carbon black and the dispersion results of carbon black.
[0055] Most of the existing dispersion test results are test results for fillers, such as the detection of carbon black disperser; the carbon black micro-dispersion detection method in rubber of the present application is based on the result of carbon black micro-dispersion, so that the dispersion of carbon black in rubber can be concretized; the carbon black dispersion detected by the carbon black disperser is consistent with the carbon black micro-dispersion result detected by the method provided in the present application, such as if the carbon black dispersion result in rubber is high, the carbon black micro-dispersion result is also high, and vice versa.
[0056] It can be concluded from the above embodiments that compared with the rubber sample image obtained by the carbon black disperser, the outline of carbon black and rubber observed by the transmission microscope provided by the present application is clearer. The microscopic dispersion data of carbon black in the obtained rubber is more accurate, and the microscopic dispersion image of carbon black is clear. This method can effectively characterize the microscopic dispersion of carbon black in rubber, and provides an effective method for studying the reinforcing performance of carbon black in rubber. It is highly operable, simple in experimental operation, short in detection cycle, low in energy consumption, and high in accuracy of detection results. It can be widely promoted and used in this field.
[0057] The above description is only a preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto. It should be pointed out that for those skilled in the art and any technician familiar with the technical field, without departing from the overall concept of the present invention, the technical solution and the inventive concept of the present invention are equivalently replaced or changed, and several changes and improvements are made, which should also be regarded as the protection scope of the present invention.
Claims
1. A method for detecting microscopic dispersion of carbon black in rubber, characterized in that: The following steps are included: (1) Sampling of vulcanized rubber; (2) Freeze the sample to -20 to -70°C below the glass transition temperature and keep it for 13 to 20 minutes, then slice the sample; (3) Take out the cut sample slices, flatten them on a glass slide with liquid paraffin oil, and then observe them under a microscope and collect pictures; (4) Calculate the area percentage of carbon black aggregates with a size of >7 μm in the image based on the image, and thus calculate the area percentage of carbon black aggregates in the rubber; Then calculate the carbon black dispersion, carbon black dispersion (%) = 100 (1-A / B), A is the area percentage of carbon black aggregates in the rubber, B is the volume percentage of carbon black in the compound, B = (density of rubber / apparent density of carbon black) × mass percentage of carbon black in rubber.
2. The method for detecting microscopic dispersion of carbon black in rubber according to claim 1, characterized in that: In step (3), a clean brush is dipped in liquid paraffin oil, and the liquid paraffin oil is brushed evenly on the glass slide. The tip of the brush dipped in liquid paraffin oil is used to take the sample slice from the sample chamber, and then the sample slice is spread and flattened on the glass slide with the tip of the brush.
3. The method for detecting microscopic dispersion of carbon black in rubber according to claim 1, characterized in that: In step (3), the dispersion of carbon black in the sample slice is observed under a microscope using transmitted light, and images are collected. For one sample slice, at least 10 images at different positions are collected. In step (4), the area percentage of carbon black aggregates with a size greater than 7 µm in each image is calculated, and the average of the results of the images at different positions is taken, which is the area percentage of carbon black aggregates in the rubber.
4. The method for detecting microscopic dispersion of carbon black in rubber according to claim 1, characterized in that: In step (3), the dispersion of carbon black in the sample slices is observed under a microscope using transmitted light, and images are collected. At least two sample slices are observed for one sample, and at least 10 images of different positions are collected for each sample slice. In step (4), the area percentage of carbon black aggregates with a size greater than 7 µm in each image is calculated, and the average of the image results at different positions of each sample slice is taken, which is the area percentage of carbon black aggregates in the rubber.
5. The method for detecting microscopic dispersion of carbon black in rubber according to claim 1, characterized in that: In step (2), the sample slice thickness is 2 μm.
Citation Information
Patent Citations
Method for detecting dispersibility of filler in rubber compound material
CN107505480A
A method for measuring dispersibility of carbon black in rubber
CN109087288A
Fiber qualitative and quantitative detection device based on hyperspectral imaging technology
CN220231501U